Nonequilibrium quantum spin dynamics from two-particle irreducible functional integral techniques in the Schwinger boson representation - Schuckert, Alexander; Piñeiro Orioli, Asier; Berges, Jürgen (Physical review, 2018)
We present a nonequilibrium quantum field theory approach to the initial-state dynamics of spin models based on two-particle irreducible (2PI) functional integral techniques. It employs a mapping of spins to Schwinger bosons for arbitrary spin interactions and spin lengths. At next-to-leading order (NLO) in an expansion in the number of field components, a wide range of nonperturbative dynamical phenomena are shown to be captured, including relaxation of magnetization in a 3D long-range interacting system with quenched disorder, different relaxation behavior on both sides of a quantum phase transition, and the crossover from relaxation to arrest of dynamics in a disordered spin chain previously shown to exhibit many-body localization. Where applicable, we employ alternative state-of-the-art techniques and find rather good agreement with our 2PI NLO results. As our method can handle large system sizes and converges relatively quickly to its thermodynamic limit, it opens the possibility to study these phenomena in higher dimensions in regimes in which no other efficient methods exist. Furthermore, the approach to classical dynamics can be investigated as the spin length is increased.